All traveling wave exact solutions of three kinds of nonlinear evolution equations - Meng, F.; Zhang, L.; Wu, Yong Hong; Yuan, W. (John Wiley & Sons Ltd., 2015)
In this article, we employ the complex method to obtain all meromorphic exact solutions of complex Klein–Gordon (KG) equation, modified Korteweg-de Vries (mKdV) equation, and the generalized Boussinesq (gB) equation at first, then find all exact solutions of the Equations KG, mKdV, and gB. The idea introduced in this paper can be applied to other nonlinear evolution equations. Our results show that all rational and simply periodic solutions are solitary wave solutions, the complex method is simpler than other methods, and there exist some rational solutions w2r,2.z/ and simply periodic solutions w1s,2.z/,w2s,1.z/ in these equations such that they are not only new but also not degenerated successively by the elliptic function solutions. We have also given some computer simulations to illustrate our main results.